Counseling on Stopping Early Marriage at Ainul Hasan Islamic Boarding School, Maron, Probolinggo - Hawa’ Hidayatul Hikmiyah; Ahmad Zainullah; Zahida I’tishoma Billah; Abd Ghafur; Nuntupa (Simfoni Ilmu Cindekia, 2025)
Early marriage is still widely found throughout the world. Every year as many as 10 million women in the world marry at the age of <18 years. This causes maternal and child mortality rates, transmission of sexually transmitted infections, and violence to increase when compared to women who marry at the age of >21 years. Therefore, it is important to provide counseling on the impact and factors of early marriage in children under the age of 19 years. The purpose of this counseling is to provide information regarding early marriage itself and the impact of early marriage. The strategies used in this service are Explanation of Stop Early Marriage, Creation of study groups, Provision of media materials to each group, Evaluation and mentoring from trainers and mentors, Evaluation of how to maintain Stop Early Marriage at the Ainul Hasan Maron Islamic Boarding School. The results of this counseling There are two concepts in the Stop Early Marriage counseling based on the delivery method, namely pull and push, each has advantages and disadvantages.